Complex couplings between joints, muscles and performance: the role of the wrist in grasping - Caumes, Mathieu (Sci Rep, 2019)
The relationship between posture, muscle length properties and performance remains unclear, because of a lack of quantitative data. Studies on grasping tasks suggested that wrist position could favour the extrinsic finger flexor in regards to their length to maximise grip force performance. The present study aimed at providing quantitative evidence of the links between wrist posture, muscle capacities and grip capabilities. It combines experimental measurements and a musculoskeletal model including the force-length relationship of the four prime muscles used in grasping. Participants exerted their maximum grip force on a cylindrical dynamometer in four different wrist postures, including one freely chosen by participants (spontaneous). A musculoskeletal model computed the muscle force level and length from motion capture and muscle activation. Results revealed that participants exerted maximum grip force spontaneously, with a loss of force when using other postures. At muscle force and length level, grip force variation seems to be associated with all the muscles under study. This observation led to a first quantitative link between power grip, posture and muscle properties, which could provide more insight into neuromechanical interaction involved when grasping. The design of ergonomic devices could also benefit from this quantification of the relationship between wrist angle and muscle length properties.